2005
DOI: 10.1111/j.1447-0756.2005.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of reversible posterior leukoencephalopathy syndrome, one with and the other without pre‐eclampsia

Abstract: Two cases of reversible posterior leukoencephalopathy syndrome (RPLS) are reported. One was a 26-year-old woman, who had pre-eclampsia and developed cortical blindness and subsequent eclampsia at 28 weeks' gestation. The other was a 27-year-old woman, who had no pre-eclampsia and developed loss of consciousness and subsequent systemic convulsion at 36 weeks' gestation. On brain magnetic resonance imaging, they both had high signal intensity on T2-weighted and fluid-attenuated inversion recovery images, and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Eclampsia is often associated with hypertension, and some believe that eclampsia is also one of the pathological conditions predisposing to RPLS/PRES (Mabie 1999). There have been many case reports of RPLS/PRES occurring after eclampsia (Hinchey et al 1996;Celik and Hascalik 2003;Finocchi et al 2005;Parisaei et al 2005;Fujiwara et al 2005), and McKinney et al (2007) reported on 76 patients with RPLS/PRES, of whom 5 (6.6%) had eclampsia.…”
mentioning
confidence: 99%
“…Eclampsia is often associated with hypertension, and some believe that eclampsia is also one of the pathological conditions predisposing to RPLS/PRES (Mabie 1999). There have been many case reports of RPLS/PRES occurring after eclampsia (Hinchey et al 1996;Celik and Hascalik 2003;Finocchi et al 2005;Parisaei et al 2005;Fujiwara et al 2005), and McKinney et al (2007) reported on 76 patients with RPLS/PRES, of whom 5 (6.6%) had eclampsia.…”
mentioning
confidence: 99%
“…Another presentation of bilateral blindness with agnosia of the visual deficit associated with PRES is Anton´s syndrome, denial of blindness. The finding of gaze palsies in the patient 3, indicated a low midbrain/high pontine lesion [65]. Cortical blindness is usually reversible.…”
Section: Discussionmentioning
confidence: 87%
“…Other authors have reported CVS with cortical blindness: PRES-cortical blindness associated with eclampsia [63][64][65][66][67][68]. PREScortical blindness associated with preeclampsia without seizures [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is uncertain whether a cause and effect relationship truly exists between the two or if these represent independent processes with some element of clinical overlap. 5 Fujiwara et al 6 and Mackinney et al 7 have reported that the cause of PRES was eclampsia in 5.5% of patients.…”
Section: Commentmentioning
confidence: 99%